The Degree of applying school principals in Mafraq governorate the good governance criteria - A Field Study on the Principals of Public Schools in Mafraq Governorate – Jordan - Al-Khawaldeh, Fayez Suleiman (Journal of Educational and Psychological Sciences, 2020)
The study aimed at finding out the Degree of applying school principals in Mafraq governorate the good governance criteria, the survey method was used, and the questionnaire was the study tool, the study sample consisting of (158) principals, the study results showed that the degree of applying school principals in Mafraq governorate good governance criteria from the standpoint of the study sample was a fair degree at an average score(3.28 From 5), Standard deviation (0.88), It also showed that there were no statistically significant differences in the estimates of the study sample individuals for the reality of competitive advantage in government schools due to the variable of the supervising authority; and for the benefit of the private authority in all fields except the field of integrity and transparency. Based on the results of the study, the researcher presented a set of recommendations and proposals to raise the degree of application of governance in schools by all available means, because the results indicate that the degree of application of governance from the point of view of school principals came with an average degree, which is an unsatisfactory indicator.